EVALUASI GUDANG LOGISTIK BERDASARKAN OBSERVASI DI BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) KABUPATEN BANTUL DALAM MENGHADAPI BENCANA ANCAMAN MEGATHRUST PANTAI SELATAN JAWA - Sianturi, Faldi Daud Suiyoso; Sulton, Adam; Sa’adah, Alfinur Insaniyati Umi; Ramadhani, Fauziah; Hafid, Anggun Abdul; SARI, SELY NOVITA; Maulana, Rizal; ridayati, (ReTII, 2024)
The Regional Disaster Management Agency (BPBD) of Bantul Regency plays a crucial role in disaster preparedness, mitigation, response, and recovery in Bantul, Yogyakarta. This community service project was conducted to evaluate the logistics warehouse management of BPBD Bantul Regency in addressing the potential threat of earthquakes and tsunamis caused by the megathrust along the southern coast of Java. The study was carried out through direct observation of the logistics warehouse and semi-structured interviews with BPBD staff during the period from May to August 2024. Observations revealed that BPBD Bantul Regency faces challenges related to limited storage space and overcrowded items, which may slow down the logistics distribution process during emergencies. Additionally, the logistics management system does not fully comply with the standards set out in BNPB Head Regulation No. 06 of 2009 on Warehouse Guidelines. To enhance preparedness, recommendations include improvements in warehouse organization, upgrading the logistics management system, and providing adequate equipment. These steps are expected to increase the efficiency and effectiveness of BPBD in handling disaster logistics, ensuring faster and more targeted distribution, and supporting optimal disaster management in Bantul Regency